Banking Union in the EU – Essence, Reasons for Establishment, Pillars, Effects and Challenges - Tabakov, Pavel (Research Papers, 2023)
The study examines the origination of the economic integration in Europe and the path towards the establishment of an Economic and Monetary Union. The reasons for the establishment of the Banking Union, its nature and structure are explored through applying the system analysis. The main pillars of the Banking Union, their degree of completion, the bodies responsible for the performance of their main functions and the effects sought from their functioning are presented. The main challenges facing the Banking Union, the priority areas for development and the expected benefits of completing its main elements with a view to achieving a stronger Economic and Monetary Union in Europe are outlined.
Keywords: Banking; European; Mechanism; Supervisory; Rulebook; Scheme; Union